Relationship of sperm protamine content with bull breeding soundness evaluation and sperm DNA damage - Mohamed Abbad Alfadel, Fatima (2022)
Protamine is a major nuclear component in mature spermatozoa known to be responsible for paternal genome protection through its roles in sperm chromatin condensation and DNA stability. Bull breeding soundness evaluation (BBSE) is the common method used to predict male fertility. This study aimed to assess the sperm protamine content using three different techniques and determine its correlation with BBSE and traditional semen quality parameters. Also to examine the role of sperm protamine in sperm DNA stability and resistance to cryodamage. Five Brangus bulls from the University Putra Malaysia farm, between 3 – 8 years old and body weights ranging from 308 – 568 kg, were subjected to BBSE. A total of 35 semen samples, seven from each bull were collected using electro-ejaculation (EE) method. Protamine content was analysed using aniline blue (AB) test, chromomycin A3 stain and fluorescent microscope (CMA3-FLM), CMA3 and flow cytometry (CMA3-FCM). DNA damage was evaluated using acridine orange (AO) staining technique, and DNA fragmentation (SDF) analysed by FCM. The result of BBSE revealed that two of the five bulls examined were unsatisfactory due to low normal sperm percentages (< 70%). The same unsatisfactory bulls showed the highest level of protamine deficiency. One way ANOVA showed significant differences (P < 0.05) among the bulls in the means of protamine deficiency. A post hoc comparison disclosed that the mean values of bull B514 for protamine deficiency were significantly higher than the other bulls (P < 0.05). Negative significant relationship (P < 0.05) was observed between protamine deficiency and the percentages of normal sperm morphology (NS) and progressive motility (PM). Both AB and CMA3-FLM tests correlated significantly (P < 0.01) with CMA3-FCM (standard gold), but AB test exhibited the higher correlation. Therefore, AB test was used to investigate the relationship between sperm protamine deficiency and sperm morphological abnormalities. A significant (P < 0.01) positive correlation was found between AB positivity and proximal cytoplasmic droplets (PD), tail and head abnormalities (T/H), pyriform heads (Py), knobbed acrosome (KA), vacuoles and teratoid (V/T). No significant correlation was found between AB positivity and mid piece (MP) or swollen acrosome (SA). Sperm protamine deficiency was significantly (P < 0.01) correlated with SDF. Sperm protamine deficiency assessed by CMA3-FCM showed the highest predictive value for SDF followed by AB test, while CMA3- FLM exhibited the lower predictive value. The effect of protamine content (CMA3-FLM) on sperm DNA integrity (AO staining) after thawing in three different times (0, 2, 4 hour) of incubation at 37°C was investigated. The results of sperm DNA damage were differed significantly across the three time points, affected by the sperm protamine content for each bull’s group. Post hoc pairwise comparison showed an increased DNA damage in bulls with lower protamine values. The findings of this study concluded that sperm protamine can be used as a useful biomarker to predict semen quality and male potential fertility. Hence, it will be of benefit if included as additional parameter of the BBSE.